Surface-engineered nanostructured high-entropy alloys for advanced electrocatalysis - Jian Cai; Han Zhu (Communications Materials)
Abstract High entropy alloys (HEAs), with their highly tunable compositions and unique physicochemical properties, hold significant promise as advanced materials for electrocatalysis. Since catalytic reactions primarily occur at the catalyst surface, optimizing surface properties is paramount for maximizing the performance of nanostructured HEAs (nHEAs) in electrocatalytic applications. This review highlights the critical role of surface optimization and explores strategies such as composition regulation, phase engineering, dimensional control, heterogeneity design, and defect engineering as crucial avenues for fine-tuning nHEAs surface properties. These advancements enable nHEAs to achieve superior activity and durability across diverse electrocatalytic reactions, including water electrolysis, carbon- and nitrogen-based conversions, and the conversion of small organic molecules. We also explore the challenges and future research directions, emphasizing the transformative potential of nHEAs in sustainable energy technologies through innovative surface design.